2012
DOI: 10.1117/12.919743
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral image segmentation using spatial-spectral graphs

Abstract: Spectral graph theory has proven to be a useful tool in the analysis of high-dimensional data sets. Recall that, mathematically, a graph is a collection of objects (nodes) and connections between them (edges); a weighted graph additionally assigns numerical values (weights) to the edges. Graphs are represented by their adjacency whose elements are the weights between the nodes. Spectral graph theory uses the eigendecomposition of the adjacency matrix (or, more generally, the Laplacian of the graph) to derive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…To understand the correlation between influence of superpixel and proposed approaches, the Gulfport dataset was over-segmented into about seven thousand superpixels having similar sizes using a Normalized Cut method. 9 Then, the rest of experiment was very similar with single point influence experiment with one difference which is instead of computing the target proportion of all points in each superpixel, we relied on the largest target proportion in each superpixel as the surrogate influence metric. This process is outlined in Alg.…”
Section: Superpixel Influence Experimentsmentioning
confidence: 99%
“…To understand the correlation between influence of superpixel and proposed approaches, the Gulfport dataset was over-segmented into about seven thousand superpixels having similar sizes using a Normalized Cut method. 9 Then, the rest of experiment was very similar with single point influence experiment with one difference which is instead of computing the target proportion of all points in each superpixel, we relied on the largest target proportion in each superpixel as the surrogate influence metric. This process is outlined in Alg.…”
Section: Superpixel Influence Experimentsmentioning
confidence: 99%
“…Finally, k-nearest neighbors and thresholding are commonly used in order to set to zero small weights in W [22]. The authors of [5,20,21] propose different strategies for defining an affinity matrix that takes into account both the spatial and the spectral information of a pixel.…”
Section: Hyperspectral Image To Graph Mappingmentioning
confidence: 99%
“…Recent research 7-9 has shown that due to spatial correlations in hyperspectral imagery (especially in high resolution hyperspectral imagery), spatial information should be included, or fused, with the spectral information in order to more adequately represent the properties of the image data in the lower-dimensional space. Incorporating spatial information has been approached from multiple fronts: modifying the structure of the graph, 7, 8 modifying the edge weights, 9 or fusing spatial and spectral Laplacian matrices and/or their generalized eigenvectors. 8 We propose a different generalization of the LE algorithm for dimensionality reduction of hyperspectral imagery in a manner that fuses spatial and spectral information.…”
Section: Introductionmentioning
confidence: 99%